The story of English in India - Krishnaswamy, N. (Foundation Books, 2006)
With globalization, English has become an economic necessity and Indians have realized that they have the English advantage over many other countries like China and Japan. India has shed its colonial complexes towards English and has come to terms with the language; Indians have separated the English language from the English. The Story of English in India presents historical facts in a socio-cultural framework. The book is a must for all teachers and students of English; it will be useful for all those interested in the politics of language and education in India
Title from publisher's bibliographic system (viewed on 02 Oct 2015)
Keywords: Geschichte; Englisch; Gesellschaft; English language / India / History; English language / Study and teaching / India; English language / Social aspects / India; Indien